2014
DOI: 10.1589/jpts.26.1561
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of an Aerobic Exercise Program and the Personality Characteristics of Patients with Fibromyalgia Syndrome: A Pilot Study

Abstract: [Purpose] The aim of this study was to assess the effectiveness of a 6-week aerobic exercise program on pain, physical function, and psychological status, and to evaluate the personality characteristics of fibromyalgia syndrome (FMS) patients. [Subjects and Methods] Fourteen women with FMS were enrolled. They were trained for a 6-week home-based aerobic exercise program. The Fibromyalgia Impact Questionnaire, the Beck Depression Inventory, the visual analog scale of pain and sleep quality were measured at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
1
14
1
1
Order By: Relevance
“…[33] However, despite the fact that the mildto-moderate intensity of the exercises was adequate in both environments, no improvement was found in the SPRI-L group, consistent with a previous study. [14] In the present study, we found an increase in aerobic capacity in both groups (pool-based and land-based environments), although in the pool-based group these results were not significant. Previous studies have also shown similar significant improvements in the aerobic capacity.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…[33] However, despite the fact that the mildto-moderate intensity of the exercises was adequate in both environments, no improvement was found in the SPRI-L group, consistent with a previous study. [14] In the present study, we found an increase in aerobic capacity in both groups (pool-based and land-based environments), although in the pool-based group these results were not significant. Previous studies have also shown similar significant improvements in the aerobic capacity.…”
Section: Discussioncontrasting
confidence: 71%
“…[12] Most of the studies on physical exercise and interventional programs in FM patients have focused on the aerobic capacity and/or muscular strength. [13] Aerobic exercise produces positive effects on FM patients, [14] while the strength exercise not always influence positively on FM symptoms. [13] Furthermore, FM has a profound impact on the patient life, causing a decline in the quality of life, which negatively affects social and professional functions.…”
mentioning
confidence: 99%
“…Aerobic endurance exercises for 12 weeks were found to have a positive effect on the fitness and well-being of FMS patients. 34 Vural et al 35 reported that aerobic exercise in the form of a six-week home program was effective on sleep quality, physical function, and signs of depression in patients with fibromyalgia.…”
Section: Discussionmentioning
confidence: 99%
“…Yoga has been reported as a safe and cost-effective intervention for managing pain (Nespore, 1991;Evan et al, 2008;Sharma et al, 2013;Büssing et al, 2012;Latha et al, 1987). Recent evidences interlink the physical and psychological benefits of yoga through the mechanisms of down-regulation of the hypothalamic-pituitary-adrenal axis and the sympathetic nervous system (Damodaran et al, 2012;Vural et al, 2014;Bae et al, 2013). Benefit of yoga in reducing headache frequency, severity and duration of migraine without aura (Wells et al, 2014;Peter et al, 2013;John et al, 2007) and tension type headache (Menon, 2013) has been documented.…”
Section: Introductionmentioning
confidence: 99%